The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1093/ajcp/84.4.496
|View full text |Cite
|
Sign up to set email alerts
|

The Cefoperazone–Sulbactam Combination: In Vitro Qualities Including Beta-Lactamase Stability, Antimicrobial Activity, and Interpretive Criteria for Disk Diffusion Tests

Abstract: Three concentrations of the penicillanic acid sulfone, sulbactam were tested in combination with cefoperazone against 632 recent clinical bacterial isolates. Cefoperazone was effective alone (less than or equal to 16 micrograms/mL) against 95% of Enterobacteriaceae and combined with 4 micrograms/mL sulbactam inhibited 99.5% of strains. This coverage of enteric bacilli was superior to timentin (99.1%), ceftazidime (98.2%), and tobramycin (90.9%). The minimum inhibitory concentrations (MICs) of cefoperazone-susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Previous in vitro and in vivo studies of a ␤-lactam antibiotic and sulbactam combination on bacteria producing ESBLs showed variable responses [6,7,11,[26][27][28][29][30][31][32][33][34]. In this study, piperacillin/sulbactam at a ratio of 2:1 significantly decreased the rate of ESBL-producing non-susceptible E. coli from 100% to 50% and decreased the MIC 50 from >128 mg/L to 16 mg/L compared with piperacillin alone.…”
Section: Discussionmentioning
confidence: 49%
“…Previous in vitro and in vivo studies of a ␤-lactam antibiotic and sulbactam combination on bacteria producing ESBLs showed variable responses [6,7,11,[26][27][28][29][30][31][32][33][34]. In this study, piperacillin/sulbactam at a ratio of 2:1 significantly decreased the rate of ESBL-producing non-susceptible E. coli from 100% to 50% and decreased the MIC 50 from >128 mg/L to 16 mg/L compared with piperacillin alone.…”
Section: Discussionmentioning
confidence: 49%
“…The antibacterial eefect of Cep and a combined action of Cef + Sul individually has already been assessed in vitro and in vivo on bacteria producing ESBLs (Jones et al 1985;Drew et al 1998). The interest in using Sul as a suicide inhibitor lies in the fact that it is available independently of β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…In this procedure synergy is defined as a fourfold reduction in MIC for both components (107). Standard procedures for disk diffusion susceptibility testing have been outlined for Augmentin (a combination of 2 parts amoxicillin to 1 part clavulanic acid) (67), Timentin (a combination of 15 parts ticarcillin to 2 parts clavulanic acid) (66,78), cefoperazone-sulbactam (79), and ampicillin-sulbactam (17). However, a cautionary note has been reported, indicating that susceptibility test results may differ according to the medium used.…”
Section: Synergistic Activity Of Inhibitorsmentioning
confidence: 99%